LEGAL ANALYSIS OF THE VALIDITY OF INTERNATIONAL CONTRACTS IN FOREIGN LANGUAGES: A STUDY OF DECISION NUMBER 135/PDT/2020/PT.DKI - Miranti; Rouli Anita Velentina (Catalist Indo Publisher, 2026)
This study aims to analyze the validity of international contracts drafted in a foreign language without an official translation into Bahasa Indonesia, based on the Decision of the Jakarta High Court Number 135/PDT/2020/PT.DKI. The main issues discussed are: (1) how Indonesian positive law regulates the use of language in international contracts involving Indonesian parties, and (2) how the judges interpret the obligation to use Bahasa Indonesia and its implications for the principle of freedom of contract. The research employs a normative juridical method, using both a statute approach and a case approach.The findings indicate that the court strictly interpreted Article 31 of Law Number 24 of 2009 as a formal requirement for contracts involving Indonesian parties. Consequently, contracts drafted solely in a foreign language without an Indonesian version are deemed formally defective and cannot be used as a legal basis in court proceedings. This approach reflects the protection of national interests and legal sovereignty but creates tension with universal principles of international contract law such as freedom of contract and pacta sunt servanda. Therefore, a harmonization between national law and international contract law principles is essential to achieve a balance between national legal certainty and global business flexibility. It is also recommended that the government issue a clearer implementing regulation for Article 31 of the Language Law to prevent legal uncertainty for foreign investors operating in Indonesia.